2019
DOI: 10.1098/rstb.2018.0313
|View full text |Cite
|
Sign up to set email alerts
|

A whitefly effector Bsp9 targets host immunity regulator WRKY33 to promote performance

Abstract: Whiteflies, Bemisia tabaci (Hemiptera), are pests causing economic damage to many crops, capable of transmitting hundreds of plant vector-borne viruses. They are believed to secrete salivary protein effectors that can improve vector colonization and reproductive fitness in host plants. However, little is known about effector biology and the precise mechanism of action of whitefly effectors. Here, we report a functional screening of B. tabaci salivary effector proteins (Bsp) capable of modulating plant innate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 45 publications
1
56
0
1
Order By: Relevance
“…Besides exploiting the indirect antagonistic relationship between SA and JA, the salivary effectors of herbivores can directly target JA signaling components to circumvent plant defenses during feeding. We identified that the whitefly salivary effector Bsp9 (also reported as Bt56) interacts with the JA-regulated WRKY33 transcription factor, which positively regulates plant resistance against whiteflies by inducing the expression of the PDF1.2 gene [69]. Another effector HARP1 from cotton bollworm oral secretions can interact with JAZ repressors to prevent COI1-mediated JAZ degradation, thus blocking the JA mediated host defense [70].…”
Section: The Herbivore Manipulation Of Ja Signalingmentioning
confidence: 99%
“…Besides exploiting the indirect antagonistic relationship between SA and JA, the salivary effectors of herbivores can directly target JA signaling components to circumvent plant defenses during feeding. We identified that the whitefly salivary effector Bsp9 (also reported as Bt56) interacts with the JA-regulated WRKY33 transcription factor, which positively regulates plant resistance against whiteflies by inducing the expression of the PDF1.2 gene [69]. Another effector HARP1 from cotton bollworm oral secretions can interact with JAZ repressors to prevent COI1-mediated JAZ degradation, thus blocking the JA mediated host defense [70].…”
Section: The Herbivore Manipulation Of Ja Signalingmentioning
confidence: 99%
“…One is that the host protein may be repressed e.g. via salivary effector Bsp9 of whitefly that shuts down host defense system reported previously (Wang et al, 2019). Since whitefly herbivory itself can activate plant defense instead of suppression, this explanation seems most unlikely.…”
Section: Resultsmentioning
confidence: 89%
“…The leucine-rich repeat protein kinase PEP RECEPTORs (PEPR1/PEPR2) are believed to sense the damage caused by herbivore feeding on plant cell (Huffaker et al, 2006). Besides, we observed that the expression of Arabidopsis PEPR1 was induced by whitefly feeding (Supplementary Figure 2A) or by the presence of Arabidopsis Pep1, a 23-amino acid endogenous peptide (Wang et al, 2019). The facts that Arabidopsis PEPR1/PEPR2 is highly expressed in plant vascular (Bartels et al, 2013), where whiteflies and begomoviruses infect (Yang et al, 2019), prompts us to hypothesize that PEPRs are one major perception machinery to sense whitefly infestation for plant cell.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations